THE EFFECT OF ECO-ENZYME ON BIOMASS PRODUCTION OF Lemna sp. IN GIANT GOURAMI (Osphronemus gouramy) CULTURE SYSTEMS - Naufal Arif Budiman; Saberina Hasibuan; Rodhi Firmansyah (Asian Journal of Aquatic Sciences, 2025)
Giant gourami (Osphronemus gouramy) is one of Indonesia's most valuable freshwater fish species; however, its aquaculture development is constrained by slow growth and low survival rates. Improving water quality through the use of aquatic plants such as Lemna sp. and the application of eco-enzymes is essential. The development of Lemna sp. depends on nutrient availability, especially nitrogen (N), phosphate (P), and potassium (K), which can be enhanced by adding an eco-enzyme. This study aimed to evaluate the effect of different eco-enzyme concentrations on Lemna sp. biomass production, specific growth rate, and water quality parameters in giant gourami culture systems. The research was conducted using an experimental method with a Completely Randomized Design (CRD) consisting of five treatments and three replications: P0 (0 ml/L), P1 (1.5 ml/L), P2 (2.5 ml/L), P3 (3.5 ml/L), and P4 (4.5 ml/L) of eco-enzyme concentration. The results showed that eco-enzyme administration significantly influenced Lemna sp. biomass. The best results were observed in treatment P4 (4.5 ml/L), which produced the highest Lemna sp. biomass (132.87 g) and specific growth rate (4.47%). Optimal water quality was recorded in treatment P4, with temperature ranging from 26.1–29.8°C, pH 5.5–8.38, dissolved oxygen 3.10–6.42 mg/L, phosphate 0.3097–0.3872 mg/L, nitrate 0.5517–10.2414 mg/L, and CO₂ 17–40 mg/L. These findings demonstrate that eco-enzyme application at 4.5 mL/L effectively enhances Lemna sp. productivity as a natural biofilter while simultaneously improving giant gourami growth performance and survival